Understanding Bourdieusian Social Capital Perspective in Student Experience: A Critical Review: A Critical Review (Teacher’s World: Journal of Education and Research, 2024)
While much of the literature on higher education focuses on issues of teaching and learning, there is a growing interest in making sense of the everyday experiences of university students. This is what is often referred to as ‘student experience’. Student experience is broadly concerned with the lives and lived experiences of university students. The aim of this paper is to discuss Bourdieusian social capital and how it is significant concept in the literature of higher education (HE) student experience. There are many approaches used in discussing student experience, but the ones reviewed in this paper are centred around Bourdieu’s use of ‘social capital’.Teacher’s World: Journal of Education and Research, 49 (2),99-107